Pengaruh Physical Evidence Dan Produk Jasa Pendidikan Terhadap Keputusan Mahasiswa Memilih Program Studi Manajemen Unimal - Lisa Noverita; Mariyudi Mariyudi (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2020)
This study aims to analyze the effect of physical evidence and educational service products on student decisions to choose a management study program at the Faculty of Economics and Business, University of Malikussaleh. The number of samples obtained in this study was 270 respondents. The data were processed using the SPSS program and analyzed using multiple linear regressions. The results of the research and data analysis were partially obtained, physical evidence and service products significantly influenced the student's decision to choose the Management Study Program at the University of Malikussaleh Lhokseumawe. Keywords: physical evidence and service products, purchase decisions